Medicinal Plants and Quantitative Ethno medicine: A Case Study from Baitadi and Darchula Districts, Far-West Nepal - Kunwar, Ripu M; Bussmann, Rainer W. (Journal of Natural History Museum, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Present study analyzed indigenous uses of medicinal plants and their informant consensus factor. Uses of Berberis asiatica for eye troubles with 1.0 consensus factor, Asparagus racemosus for galactogogue, Cordyceps sinensis as tonic and longetivity, Nardostachys grandiflora for eplilepsy and Phyllanthus emblica as diuretic with 0.97 each were highest consensus factor values and these species showed the greatest affinity to the common uses of Ayurveda and phytochemical findings. Highest informant consensus factors and greater affinities with Ayurveda and phytochemical validations provide the immense potential to identify which plants are most likely to be useful in the ailments. Key Words: Berberis asiatica, Indigenous uses, Informant consensus factor (ICF), West Nepal Journal of Natural History Museum Vol. 24, 2009 Page: 72-81